THE EFFECT OF CAPITAL STRUCTURE, LEVERAGE, COMPANY GROWTH, PROFITABILITY AND AUDIT QUALITY ON COMPANY VALUE - Isbul Waton; Rita Friyani; Misni Erwati (Universitas Nusa Cendana, 2026)
This study aims 1) To find out and obtain empirical evidence on the effect of capital structure, leverage, company growth, profitability, and audit quality on company value; 2) To find out and obtain empirical evidence on the effect of capital structure on company value; 3) To find out and obtain empirical evidence on the effect of leverage on company value; 4) To find out and obtain empirical evidence on the effect of company growth on company value; 5) To find out and obtain empirical evidence on the effect of profitability on company value; 6) To find out and obtain empirical evidence on the effect of audit quality on company value. The objects of the study were real estate and property companies listed on the Indonesia Stock Exchange for the period 2020-2022. The sample used in the study was 62 companies. The data analysis method used in the study was multiple linear regression analysis. The results of this study indicate that capital structure, leverage, company growth, profitability, and audit quality together affect company value. Based on the partial regression results, capital structure and leverage have a significant effect on company value, while company growth, profitability, and audit quality do not have a significant effect on company value. Keywords: Firm Value; Capital Structure; Leverage; Firm Growth; Profitability; Audit Quality